PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN PENGANGKUTAN DAN NIAGA BAHAN BAKAR MINYAK (BBM) BERSUBSIDI - Nadya Shahnaz (INTELIGENSIA MEDIA, 2025)
This thesis discusses law enforcement against the misuse of transportation and trade of subsidized fuel oil in Indonesia. Subsidized fuel oil (BBM) is one of the important commodities that greatly influences the economy and public welfare. However, in practice, misuse in the transportation and trade of subsidized fuel oil often occurs, resulting in state losses and injustice for the entitled community. The problems taken in this study are how the law in Indonesia regulates the transportation and trade of subsidized fuel oil, how law enforcement functions to prevent misuse of fuel oil subsidies and what constitutes the law against the misuse of transportation and trade of subsidized fuel oil. The purpose of this study is to investigate the regulations relating to subsidized fuel oil transportation and trade companies in Indonesia and to evaluate law enforcement procedures relating to violations related to the distribution and trade of fuel oil and to find obstacles to law enforcement and resolve them. The research method used is a qualitative approach with case studies, where data is collected through interviews, observations, and analysis of related documents. The results of the study indicate that there are various modes of misuse, such as modifying vehicle numbers to misuse subsidized fuel, modifying vehicle numbers to misuse which are then resold at higher prices that are not in accordance with the law. Existing law enforcement still faces various obstacles, including coordination between agencies, minimal sanctions for violators, and low public legal awareness. Based on these findings, it is recommended that the government strengthen regulations and increase cooperation between agencies in law enforcement. In addition, socialization regarding the importance of using subsidized fuel appropriately also needs to be increased to create collective awareness in maintaining state resources.